Efficacy and safety of underwater endoscopic mucosal resection for ≤20 mm superficial non-ampullary duodenal epithelial tumors: Systematic review and meta-analysis - Liu, Jixiang; Duan, Shaojie; Wang, Yichong; Peng, Hongye; Kong, Youjia; Yao, Shukun (Frontiers in Medicine, 2023)
Background and Aims: Superficial non-ampullary duodenal epithelial tumors (SNADETs) as a rare disease have gradually increased in recent years. Underwater endoscopic mucosal resection (UEMR) has emerged as a newly available option for the endoscopic resection of SNADETs. This study aimed to evaluate the efficacy and safety of UEMR for <= 20 mm SNADETs. Methods: A literature search was performed across multiple databases, including PubMed, Embase, Scopus, and Clinical trials for studies containing tumors <= 20 mm published from January 1, 2012, to August 8, 2022. Outcomes examined were the pooled rates of en bloc resection, R0 resection, adverse events, and recurrence. Subgroup analyses of the resection rate were conducted stratified by sample size and polyp size. Results: A total of 10 studies with UEMR performed in a total of 648 tumors were included for analysis. The pooled rate of en bloc resection and R0 resection was 88.2% (95% confidence interval (CI): 82.1-93.2) and 69.1% (95%CI: 62.2-76.1), respectively. The results showed pooled rate of intraoperative bleeding rate was 2.9% (95%CI: 0-9.0), delayed bleeding rate was 0.9% (95%CI: 0.1-2), recurrence rate was 1.5% (95%CI: 0-4.9). In the subgroup analysis, R0 and en-bloc resection rates were significantly higher in <10mm than 10-20mm SNADETs subgroups (R0 resection rate 83.1% vs 48.6%; en bloc resection rate 100.0% vs 84.0%, P<0.05). Conclusions: UEMR was an effective and safe technique for the optional treatment for ≤20 mm SNADETs, especially of <10mm.